A zinc-phobic porous composite membrane for realizing crystal plane manipulation, preparation method and application thereof in zinc-based liquid flow battery

By spin-coating carboxymethyl cellulose on the porous composite membrane surface of zinc-based liquid flow battery, the charge properties and ion transfer on the surface of the membrane are adjusted, and the problems of degradation of battery performance and shortening of life caused by zinc dendrites are solved, and higher ions are achieved Conductivity and battery stability.

CN117766830BActive Publication Date: 2024-12-27NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311583199.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2024-12-27
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

During the charging and discharging process of zinc-based liquid flow batteries, the membrane damage, the battery performance decreases and the cycle life is shortened due to the generation of zinc dendrites. The traditional electrically neutral porous membrane transmits OH-rate at a low rate.

Method used

By spin-coating carboxymethyl cellulose (CMC) on the surface of the porous composite membrane, the charge properties of the membrane surface are adjusted, and a negative charge zinc-reducing barrier is formed, and the local accumulation of zincate ions at the membrane-electrode interface is prevented, and the local accumulation of zincate ions at the membrane-electrode interface is promoted. Zinc is deposited on the (002) crystal surface and improves the OH-transfer channel to enhance ionic conductivity.

Benefits of technology

A dendrite-free zinc-based flow battery is realized, which improves battery performance and long-term cycle stability, extends battery life, and improves ion conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117766830B_ABST
    Figure CN117766830B_ABST
Patent Text Reader

Abstract

The present invention provides a zinc-phobic porous composite membrane for realizing crystal plane manipulation, a preparation method and its application in a zinc-based liquid flow battery, belonging to the technical field of liquid flow batteries. Carboxymethyl cellulose (CMC) is introduced to customize and optimize the charge properties of the membrane surface, and a zinc-phobic interface engineering based on electrostatic repulsion is constructed to uniformly distribute zincate ions along the membrane-electrode interface. This zinc-phobic interface engineering successfully realizes crystal plane manipulation, increases the exposure of the preferentially oriented crystal plane ((002) crystal plane) of zinc deposition, thereby obtaining a smoother zinc deposition and extending the life of the zinc-based liquid flow battery. In addition, the good wettability of the hydrophilic CMC to the electrolyte and its rich ‑OH functional groups to the carriers (OH ‑ ) The positive influence of transport kinetics synergistically ensures that the prepared membrane has high ionic conductivity. This study provides a new crystal plane manipulation approach to solve the zinc dendrite problem, thereby promoting the commercialization of zinc-based flow batteries for long-term energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a zinc-phobic porous composite membrane for realizing crystal plane manipulation, a preparation method and application thereof in a zinc-based liquid flow battery, and belongs to the technical field of liquid flow batteries. Background Art

[0002] The depletion of fossil fuels and the intensification of the greenhouse effect have made the transition to an efficient, renewable and low-carbon energy system imperative. The construction of a new power system that combines renewable clean energy and energy storage technology is one of the effective ways to achieve a clean and low-carbon energy transformation. Among the many energy storage technologies, flow battery energy storage technology, which has the advantages of safety, reliability, high cost performance, environmental friendliness and long cycle life, has become one of the preferred technologies for large-scale energy storage. In particular, zinc-iron flow batteries, which use zinc and iron, two abundant and inexpensive elements, as the main raw materials, are expected to break through in the long-term energy storage market and usher in an explosion of production capacity after solving technical bottlenecks such as the zinc dendrite problem. As one of the key core components of zinc-iron flow batteries, battery separators are easily pierced by zinc dendrites during battery charging, and their quality directly affects the battery's operating efficiency and stability. However, traditional organic porous membranes have low mechanical strength, poor anti-dendrite ability, and problems of mismatch between ion selectivity and ion conductivity, which seriously restrict the strategic layout of zinc-iron flow batteries in the future energy storage field.

[0003] Since the electrochemical reaction of the metal pair tends to occur at the membrane-electrode interface, by adjusting the properties of the surface and interface (such as hydrophilicity, roughness, rigidity, etc.), a uniform deposition process can be effectively achieved, and the formation of dendrites can be further avoided. For example, Xu et al. loaded zeolite molecular sieve nanosheets (ns-MFI) with high mechanical strength and hydrophobicity on the surface of a porous substrate, and its special fish scale arrangement can be used as a buffer layer to enhance anti-dendritic ability, while hydrophobic ns-MFI reduces the adsorption energy of the membrane surface and zincate ions, effectively regulating the distribution of zincate ions at the membrane-electrode interface, thereby achieving uniform zinc deposition (non-patent literature 1). However, the influence of the membrane surface charge on the deposition process will have an impact, and if the diaphragm surface has a certain adsorption effect on zincate ions, it will lead to an increase in zinc deposition, thereby affecting the battery operation performance.

[0004] Non-patent literature 1: Hou, Summary of the invention

[0005] The technical problem to be solved by the present invention is that during the charge and discharge process of zinc-based liquid flow batteries, the generation of zinc dendrites leads to membrane damage, battery performance degradation and shortened cycle life; the rate at which electrically neutral porous membranes transmit OH- is slightly low.

[0006] The technical concept adopted by the present invention is: by spin coating carboxymethyl cellulose (CMC) on the surface of the porous composite membrane to perform membrane surface functionalization, the surface charge properties of the membrane are further improved, and a uniform Zn(OH)4 2- Distribution, avoiding the phenomenon of excessive local zincate ion concentration caused by the "tip effect", thereby inducing zinc to expose more preferential crystal plane orientations (parallel (002) crystal planes) during deposition. In addition, under the synergistic effect of the good wettability of hydrophilic carboxymethyl cellulose to the electrolyte and the positive influence of its abundant -OH functional groups on OH-transmission kinetics, a fast transfer channel for charge-carrying ions (OH-) is formed, showing higher ionic conductivity. The present invention provides a new solution for dendrite-free alkaline zinc-based flow batteries, that is, to adjust the microenvironment charge characteristics of the membrane electrode interface by customizing and optimizing the surface charge properties of the composite membrane to achieve crystal plane manipulation.

[0007] A zinc-based liquid flow battery separator comprises a porous base membrane. A modification layer is covered on the surface of the porous base membrane. The material of the modification layer contains a modification material and a binder. The modification material contains -COOH and -OH.

[0008] The charge properties of one side of the porous base membrane are adjusted by introducing molecules with -COOH and -OH to construct a functional layer, so that the surface of the porous composite membrane has a strong negative charge. The functional layer is evenly distributed on the surface of the porous base membrane and is in contact with the zincate ions (Zn(OH)4 2- ) Based on the mutual repulsion of the Donnan effect, a zinc-repellent barrier is constructed for the porous membrane.

[0009] The base film is a porous base film with a thickness of 20 to 500 μm; the modification layer has a thickness of 0.1 to 10 μm.

[0010] The Zeta potential value of the surface of the zinc-based liquid flow battery separator is less than -10 mV, preferably less than -20 mV.

[0011] The material of the porous base membrane is selected from one or more of polysulfones, polyketones, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, polybenzimidazole, polyvinyl pyridine, polyethylene, polypropylene, chitosan, and cellulose acetate; the polymer is preferably a mixture of one or more of polyethersulfone and sulfonated polyetheretherketone.

[0012] The modifying material is selected from one or a mixture of carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, carboxylated carbon nanotubes or carboxylated chitosan; the binder is selected from one or more of Nafion, sulfonated polyetheretherketone, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene and polyimide.

[0013] The above-mentioned method for preparing the zinc-based flow battery diaphragm comprises the following steps:

[0014] Step 1, obtaining a porous base membrane;

[0015] Step 2: Disperse the modifying material and the binder in a solvent, and apply them on the surface of the porous base film, and obtain the zinc-based liquid flow battery separator after drying.

[0016] In the step 1, the base film is prepared by the following method: dispersing the polymer in an organic solvent as a casting liquid; coating the casting liquid on the surface of the substrate, and performing a film-forming treatment by a phase inversion method to obtain a porous base film; the organic solvent is selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, chloroform or dimethyl sulfoxide.

[0017] In the phase inversion method, a poor solvent for the polymer is used as a coagulation bath, and the immersion time in the coagulation bath is 1-600s; in the phase inversion method, after the membrane is treated in the coagulation bath, it is treated with an extraction solvent at a set temperature for a certain time; the temperature is 20-200°C, and the treatment time is 0.5-24h.

[0018] In step 2, the coating method is selected from flat blade coating, spray coating or spin coating; the mass ratio of the modifying material to the binder is 1:(3-8), and the binder accounts for 1-20% of the weight of the solvent.

[0019] Application of battery separators in zinc-based flow batteries.

[0020] In the application described, the modified layer faces the negative electrode of the battery.

[0021] The application also includes a method for predicting battery VE performance, including the following steps:

[0022] Determination of Fe(CN)6 in battery separators obtained under different preparation conditions 4- The permeability or surface resistance of the battery separator is determined, and the battery separator with the highest permeability or lowest surface resistance is taken as the separator with the highest VE performance prediction.

[0023] The present invention also provides a method for regulating the crystal orientation of a zinc deposit layer (002) on the surface of a diaphragm during operation of a zinc-based liquid flow battery, comprising the following steps:

[0024] Step 1, obtaining a porous base membrane;

[0025] Step 2, dispersing the modifying material and the binder in a solvent, and coating the resultant on the surface of the porous base film, and obtaining a zinc-based flow battery separator after drying;

[0026] Step 3, by increasing the loading amount of the modified material on the surface of the porous base film, the content of zinc with (002) crystal plane in the zinc deposition layer is increased.

[0027] Beneficial Effects

[0028] According to the Donnan effect, by adjusting the microenvironment charge characteristics of the membrane-electrode interface, the membrane surface and zincate ions are mutually repelled, which can effectively avoid their accumulation at certain tips, thereby achieving crystal surface manipulation. The present invention selects carboxymethyl cellulose (CMC) with rich functional groups (-COOH, -OH), uses a small amount of binder, and evenly distributes it on the surface of the porous base membrane by spin coating, wherein the -COOH functional group gives the composite membrane surface a strong negative charge. 2- The electrostatic repulsion between them makes the zincate ions follow the Donnan mechanism to stay away from the membrane surface, which in turn weakens the "tip effect" during zinc deposition and is conducive to more exposure of the preferred orientation crystal plane ((002) crystal plane) of zinc deposition. At the same time, under the synergistic effect of the good electrolyte wettability of hydrophilic CMC and the positive influence of its abundant -OH functional groups on OH-transport kinetics, the ionic conductivity of the composite membrane is improved. Ultimately, the battery equipped with the composite membrane exhibits excellent battery performance and long-term cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the construction of a porous composite membrane with a zinc-repellent functional layer by spin coating.

[0030] Figure 2 SEM and EDX characterization of porous composite membranes: a), b) P / S, c), d) P / S-Nf-CMC-400.

[0031] Figure 3 a) Porosity and b) FTIR of porous composite membranes.

[0032] Figure 4 It is a) water absorption and swelling rate, b) tensile strength and c) nanoindentation of the porous composite membrane.

[0033] Figure 5 It is a porous composite membrane of Fe(CN)6 4- Permeability test: a) test apparatus, b) permeability curve.

[0034] Figure 6 The OH of the porous composite membrane - Permeability curve.

[0035] Figure 7 Electrochemical impedance spectroscopy tests of porous composite membranes: a) conductivity, b) membrane surface resistance.

[0036] Figure 8 The electrochemical impedance spectroscopy test of Comparative Examples 1 and 2 is shown in FIG.

[0037] Fig. 9 The porous composite membrane is 80mA cm -2 Battery performance under .

[0038] Fig.10 The porous composite membrane is 40-240mA cm -2 Battery testing. a) Schematic diagram of membrane orientation, b) CE, c) VE, d) EE.

[0039] Fig.11 The battery cycle stability test of the porous composite membrane. a) Charge and discharge voltage curves of the battery loaded with P / S and P / S-Nf-CMC-400, b) enlarged view of the charge and discharge voltage curves, c) discharge capacity of the battery.

[0040] Fig.12 Digital photos, SEM images, and EDX spectra of the porous composite membrane surfaces after battery cycling stability test: a) P / S, b) P / S-Nf-CMC-400.

[0041] Fig.13 The cells with different membranes are at 80 mA cm -2 Long cycle testing at different current densities.

[0042] Fig.14 SEM images of zinc deposition on carbon felt after cycling of batteries equipped with different membranes for a period of time: a) P / S, b) P / S-Nf-CMC-400, c) P / S-Nf-CMC-500, d) P / S-Nf-CMC-800, e) P / S-Nf-CMC-1000.

[0043] Fig.15 Wiener scan images of zinc deposition on carbon felt after cycling of cells with different membranes for a period of time: a) P / S, b) P / S-Nf-CMC-400, c) P / S-Nf-CMC-500, d) P / S-Nf-CMC-800, e) P / S-Nf-CMC-1000.

[0044] Fig.16 The zinc deposition orientation on the carbon felt of the battery equipped with different membranes at the end of the cycle. a) Schematic diagram of zinc deposition orientation, b) XRD test results, c) (002) crystal plane and (100) crystal plane XRD diffraction peak intensity ratio.

[0045] Fig.17 It is a Zeta potential test on the surface of porous composite membrane.

[0046] Fig.18 These are the test results of quartz crystal microbalance (QCM) for different film layers.

[0047] Fig.19 It is a potential energy scan between different molecules and zincate ions.

[0048] Fig. 20 Schematic diagram of the mechanism by which CMC regulates zinc deposition behavior. DETAILED DESCRIPTION

[0049] The present invention selects carboxymethyl cellulose (CMC) with rich functional groups (-COOH, -OH), uses a small amount of binder, and evenly distributes it on the surface of the porous base film ( Figure 1 ). The presence of a large number of -COOH functional groups effectively regulates the surface charge properties of the composite membrane, making it have a strong negative charge. The zincate ions follow the Donnan mechanism and repel each other with the negatively charged membrane surface, moving away from the membrane surface. This in turn weakens the "tip effect" during zinc deposition, which is conducive to more exposure of the preferred orientation crystal plane ((002) crystal plane) of zinc deposition. At the same time, the good electrolyte wettability of hydrophilic CMC and its abundant -OH functional groups are very favorable to OH - The positive effects of transport kinetics synergistically improve the ionic conductivity of the composite membrane. Ultimately, the battery equipped with the composite membrane exhibits excellent battery performance and long-term cycle stability.

[0050] Example 1 Preparation of sulfonated polyetherketone

[0051] Sulfonated polyetherketone (SPEEK) is prepared by direct sulfonation of PEEK with sulfuric acid (98%) at 50°C for 5 hours (Non-Patent Document 2). 1 The sulfonation degree (DS) of the prepared SPEEK was about 67% as determined by H NMR.

[0052] Non-patent literature 2: J.Xi, Z.Li, L.Yu, B.Yin, L.Wang, L.Liu, X.Qiu, L.Chen Effect of degree of sulfonation and casting solvent on sulfonated poly(ether etherketone)membrane for vanadium redox flow battery J.Power Sources,285(2015),pp.195-204,10.1016 / j.jpowsour.2015.03.104.

[0053] Example 2 Preparation of porous base membrane

[0054] The porous base membrane (P / S) was prepared by phase inversion method. Polyethersulfone (PES) and sulfonated polyetherketone (SPEEK) were added to the solvent DMAc, and then the mixture was ball-milled and ultrasonically treated, and then left to stand for defoaming to form a uniform casting solution. The total polymer concentration of the casting solution was 35wt%, of which SPEEK accounted for 20wt% and the rest was PES.

[0055] The casting solution was poured onto a flat glass plate and a flat film scraper was used to prepare the film at room temperature. The glass plate was then immersed in water until the film was automatically peeled off after the phase inversion was completed. The obtained film was soaked in isopropanol for 30 minutes and then evaporated at room temperature for 2 hours to ensure complete volatilization of the isopropanol. Finally, the film was stored in deionized water for use. The thickness of the prepared porous base film was 70±5μm.

[0056] Example 3 Construction of zinc-phobic functional layer

[0057] The CMC suspension (denoted as Nf-CMC) was prepared by adding CMC-V (DS = 0.7MW = 90000) powder to a 5wt% Nafion solution (the mass ratio of CMC / Nafion was 1 / 5), followed by ultrasonic treatment for 30 minutes, wherein the Nafion solution was used as a binder. The prepared P / S base membrane (3.5cm 2 ) was coated with Nf-CMC, and a series of porous composite membranes with different functional layer thicknesses were prepared by changing the spin coating amount of Nf-CMC (400, 500, 800, 1000 μL). Then it was placed in an oven and dried at 60 ° C for 6 hours, and finally stored in deionized water for use.

[0058] Comparative Example 1 Preparation of PES / SPEEK membrane

[0059] The difference from Example 3 is that there is no zinc-repellent functional layer, that is, the original P / S film.

[0060] Comparative Example 2: Porous composite membrane with pure Nafion functional layer

[0061] The difference from Example 3 is that CMC is not added to the spin coating solution, and 5 wt % Nafion solution is directly used. The preparation method is the same as that of Example 3.

[0062] Comparative Example 3: Using high-substituted CMC to construct a porous composite membrane with zinc-repellent functional layer

[0063] The difference from Example 3 is that CMC-V is replaced by highly substituted CMC-I (DS=0.9MW=700000) and CMC-III (DS=0.9MW=250000), the number of -COOH functional groups is increased and the number of -OH functional groups is reduced, and the obtained porous composite membranes are respectively recorded as P / S-Nf-CMC (H1) and P / S-Nf-CMC (H2).

[0064] Film morphology characterization

[0065] The digital photos show that the morphology of the film did not change after spin coating with CMC ( Figure 2 A and Figure 2 c). The prepared P / S-Nf-CMC film was translucent and uniform (spin coating volume 400μL) without obvious defects. The surface and cross-sectional morphology of the film were characterized by field emission scanning electron microscopy (SEM), and the elemental composition of the film was detected by energy dispersive X-ray spectrometry. The cross-sectional SEM and EDX ( Figure 2 d) proves the successful spin coating of the CMC functional layer, and there is no obvious infiltration of the spin coating liquid. The overall cross section still retains the sponge-like porous structure consistent with the original P / S film ( Figure 2 b), and the porosity has no significant change compared with the P / S membrane ( Figure 3 a). The surface SEM of the membrane ( Figure 2 c) shows that its surface is similar to the original P / S film ( Figure 2 There is no significant difference compared with a), which indicates that the Nf-CMC mixed solution is evenly spin-coated on the film surface and does not change the structure of the original P / S film. The Fourier transform infrared spectroscopy (FTIR) test results show that at 1720cm -1 The typical C=O characteristic peak of carboxyl group (-COOH) appears at Figure 3 b), which also proves that CMC is successfully loaded on the surface of the P / S membrane.

[0066] Mechanical properties testing of membranes

[0067] The results of the membrane water swelling test ( Figure 4a) shows that the introduction of a thin and dense Nf-CMC functional layer on the porous membrane surface effectively inhibits the swelling of the membrane, allowing the membrane to maintain a stable morphology in practical applications. However, as the amount of spin-coated Nf-CMC mixed solution increases, the hydrophilic CMC causes the membrane to absorb more water, resulting in a slight increase in the swelling rate of the membrane. At the same time, the introduction of CMC can effectively improve the tensile strength of the membrane, and the transverse mechanical tensile strength of the membrane is significantly improved ( Figure 4 b). In addition, in order to further verify the longitudinal impact resistance of the film, a secondary pressure nanoindentation characterization was performed. Figure 4 As shown in Figure c, as the functional layer on the surface of the porous membrane thickens, the hardness of the prepared membrane continues to increase, and is much higher than that of the original membrane. The significantly improved film hardness will ultimately improve the membrane's resistance to dendrite puncture and ensure the safe and stable operation of the battery.

[0068] Membrane selective transport capability test

[0069] The Nf-CMC functional layer is beneficial to accelerate the selective transport of ions. On the one hand, due to the presence of the additional dense functional layer, the barrier capacity of the P / S-Nf-CMC membrane for active ions is significantly enhanced compared with the P / S-based membrane. On the other hand, the hydrophilic CMC and its rich -OH functional groups are conducive to the rapid transport of OH- through standard diffusion (car-borne mechanism) and proton hopping (Grotthuss mechanism).

[0070] The diffusion method ion permeability test process used is as follows:

[0071] Fe(CN)6 4- The permeability of ions through the membrane is determined using a pair of diffusion cells separated by a membrane. The left cell is filled with 0.4 mol L -1 3 mol L of K4Fe(CN)6 -1 NaOH solution (volume: 50 mL), and the right half of the cell was filled with 0.4 mol L -1 3 mol L of K2SO4 -1 NaOH solution (volume: 50 mL) was added to balance the ionic strength on both sides. During the experiment, the solutions in both half cells were vigorously stirred with a magnetic stirrer to avoid the influence of concentration polarization. 3 mL of sample solution was collected from the right half cell regularly, and then 3 mL of fresh K2SO4 solution was added to the right half cell to keep the solution volume stable. The concentration of K4Fe(CN)6 in the sample solution was detected using a UV-visible spectrophotometer. Fe(CN)6 4- The permeability of the membrane was calculated according to Fick's diffusion law. The permeability of hydroxide ions through the membrane was also determined in a similar manner. The left half of the cell was filled with 50 mL of 3 mol L -1NaOH solution, the right half of the cell is filled with deionized water. The hydroxide ion concentration in the right half of the cell with different diffusion times is measured by a pH meter. Diffusion method for Fe(CN)6 4- and OH - Devices with different membrane permeabilities such as Figure 5 As shown in a.

[0072] By diffusion method ( Figure 5 a) Measurement of Fe(CN)6 4- The permeability curve ( Figure 5 b) fully proves that the P / S-Nf-CMC membrane has improved barrier capacity for active ions. In addition, all P / S-Nf-CMC membranes show faster OH than P / S membranes. - Transfer rate( Figure 6 ). Electrochemical impedance spectroscopy (EIS) experiment ( Figure 7 a and b) further revealed that the P / S-Nf-CMC membrane has higher ionic conductivity than the P / S-based membrane ( Figure 7 a) and lower surface resistance ( Figure 7 b). It is worth noting that there is an optimal spin coating amount of Nf-CMC, which is about 400 μL. This is because, as the spin coating amount increases, the thickness of the functional layer increases, which prolongs the OH - transmission path, reducing its transmission capacity. In addition, the presence of more hydrophilic CMC will enhance the wettability of the membrane to the electrolyte, thereby increasing the chance of active ions passing through the membrane, and the ion selectivity of the prepared membrane will also decrease slightly. Based on the above tests, the present invention also provides a method for predicting battery VE performance, comprising the following steps: determining the Fe(CN)6 4- The permeability or surface resistance of the battery separator is determined, and the battery separator with the highest permeability or lowest surface resistance is taken as the separator with the highest VE performance prediction.

[0073] In order to further verify the benefits of hydrophilic CMC and its abundant -OH functional groups, pure Nafion solution (denoted as Nf) and Nf-CMC solutions (denoted as Nf-CMC (H1) and Nf-CMC (H2)) prepared from two CMCs with higher substitution degree (the number of -OH functional groups is less than that of the CMC selected in Example 3) were used to construct functional layers. Figure 8 The EIS test of the ionic conductivity of the composite membranes with Nf-CMC(H1) and Nf-CMC(H2) functional layers (denoted as P / S-Nf-CMC(H1)-500 and P / S-Nf-CMC(H2)-500) showed that the gradual decrease in the number of -OH functional groups did have an effect on the OH -The transport kinetics via the Grotthuss mechanism was slightly adversely affected. In addition, the ionic conductivity of the composite membrane with Nf functional layer (denoted as P / S-Nf-500) was slightly higher than that of the P / S membrane, but much lower than that of the P / S-Nf-CMC-500 membrane. This result fully confirms that hydrophilicity is essential for the rapid OH transport following the on-board mechanism. - Importance of transmission Figure 8 ). After a three-way comparison, it was found that the hydrophilicity of CMC plays a greater role in achieving the rapid transport of OH-.

[0074] Evaluation of cell efficiency and zinc dendrite-free performance

[0075] In order to verify the applicability of the prepared P / S-Nf-CMC membrane in alkaline zinc-iron flow battery (AZIFB), battery performance tests were carried out.

[0076] The process of battery assembly and performance testing is as follows:

[0077] A diaphragm to be tested is sandwiched between two carbon felt electrodes, which are clamped by two graphite plates, and then all these parts are fixed between two acrylic plates to assemble the battery assembly. The effective area of ​​the electrode is 3×3cm 2 . 10mL 0.6M K4Fe(CN)6+5M NaOH and 10mL 0.3M Zn(OH)4 2- +5M NaOH solution was used as positive and negative electrolyte. During battery operation, a peristaltic pump was used to force the positive and negative electrolytes to circulate in their respective reaction chambers to participate in the electrochemical reaction. The charge and discharge cycle test was performed using ArbinBT 2000: the charging process was controlled by a fixed charging time to maintain a constant charging capacity, while the discharge process was terminated by setting a cut-off voltage of 0.1V. The coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of the battery were calculated by the following equations:

[0078]

[0079]

[0080]

[0081] Among them C d and C c are the discharge capacity and charge capacity respectively, E d and E C are the discharge energy and the charge energy respectively.

[0082] First, at 80 mA cm -2 The cells equipped with different membranes were tested. Fig. 9All batteries have relatively high CE, proving that these membranes have good ion selectivity. The battery VE reaches a peak at 400 μL of spin coating, which is consistent with the test results of OH-permeability and EIS; further confirming the correctness of the above prediction method, through which the battery performance of the battery separator obtained under different conditions when applied to flow batteries can be predicted using simple test conditions, improving the efficiency of experimental optimization.

[0083] In addition to confirming that the prepared porous composite membrane has good battery efficiency, solving the zinc dendrite problem is of utmost importance to ensure the efficient and stable operation of ZFBs, especially considering that the operating conditions of high current density will aggravate the growth of zinc dendrites. In order to further verify the rationality and superiority of the P / S-Nf-CMC membrane in alleviating the zinc dendrite problem, the operating stability of AZIFBs equipped with different membranes was studied. Since the Nf-CMC functional layer is only loaded on one side of the porous base membrane, this side surface is facing the negative electrode (the side where zinc plating / stripping occurs) during battery operation to maximize the benefit ( Fig.10 a). Fig.10 As shown in Figures bd, all cells equipped with P / S-Nf-CMC membranes showed a decrease in the current density (from 40 mA cm -2 Up to 240mAcm -2 ) can maintain stable operation even when the current density is higher than 200mA cm -2 Even more encouragingly, when the current density was reduced to 80 mA cm -2 The above results prove that even at high current density, where zinc dendrites are more likely to grow, the battery using the P / S-Nf-CMC membrane can still maintain a stable operating state without the problem of dendrites piercing the membrane. In contrast, when the current density reaches 200 mA cm -2 Even worse, when the current density dropped again to 80 mA cm -2 When the P / S membrane structure is completely destroyed, the battery performance will be irreversibly reduced.

[0084] Afterwards, at 80 mA cm -2 A 100-hour cycle stability test was conducted under low temperature to further study the ability of the P / S-Nf-CMC film to regulate the zinc deposition behavior to ensure stable battery operation. Fig.11As can be seen from a), the battery using the P / S-Nf-CMC membrane can maintain a relatively low charging voltage value throughout the measurement process. In contrast, the battery using the P / S membrane continued to increase its charging voltage value after nearly 50 hours of stable operation, indicating that the stable operation state of the battery was destroyed and a serious imbalance occurred during the charge and discharge process. After the test, the membranes were removed from the battery device to study their morphology. It was found that there was a large amount of zinc residue on the surface of the P / S membrane ( Fig.12 a), these zinc residues come from zinc dendrites. Zinc dendrites continue to grow, eventually penetrate the membrane and remain in the pores, which is the culprit for the increase in charging voltage ( Fig.11 b), they hinder the transfer of charged ions and increase the resistance of the membrane. Worse still, they become "dead zinc" and cannot participate in subsequent cycles, causing the battery discharge capacity to decay ( Fig.11 c). However, the morphology of the P / S-Nf-CMC membrane remained intact with no zinc residue ( Fig.12 b), indicating that the Nf-CMC functional layer successfully achieved Zn dendrite / no accumulation performance with stable discharge capacity.

[0085] Finally, the cell equipped with P / S-Nf-CMC membrane had a -2 Maintains an extremely long operating life ( Fig.13 ), can stably cycle more than 3000 times (>1000 hours), which is much higher than the original P / S membrane (~500 times) and P / S-Nf-500 membrane (~900 times). At the same time, the average performance of its battery is stable at CE~98.5%, EE~79.9%, and VE~81.1%.

[0086] Regulatory effect of Nf-CMC functional layer on zinc deposition behavior

[0087] In order to study the effect of Nf-CMC functional layer on zinc deposition behavior in detail, the morphology of zinc deposition on carbon felt after the battery equipped with different membranes was cycled for a period of time was first studied in depth. The morphological characteristics of the zinc coating were characterized by field emission scanning electron microscopy (FE-SEM). SEM images showed that the zinc deposition on the carbon felt of the battery using P / S membrane showed a large number of typical needle-like morphologies ( Fig.14 a). However, there is no obvious sharp zinc deposition on the carbon felt of the battery using P / S-Nf-CMC membrane ( Fig.14 It is worth noting that with the increase of Nf-CMC spin coating amount, the zinc deposition gradually tends to a flat masonry structure. In addition, the surface roughness of zinc deposition on carbon felt was analyzed by micro-nano scanning analyzer, which also confirmed that the deposition of metal zinc on battery carbon felt using P / S-Nf-CMC film is smoother than that on P / S base film ( Fig.15 ).

[0088] Zinc metal has a typical hexagonal structure, with the main orientations being (002), (100) and (101) crystal planes ( Fig.16 a), where the (002) crystal plane is the preferred orientation for forming a relatively flat zinc deposition. On this basis, an X-ray diffractometer (XRD) was introduced to study the crystal plane orientation of zinc deposition on carbon felt. Fig.16 As shown in b, for zinc deposition on battery carbon felt using P / S film, the diffraction peak intensity corresponding to the (100) and (101) crystal planes is relatively high. However, for zinc deposition on battery carbon felt using P / S-Nf-CMC film, the diffraction peak intensity corresponding to the (002) crystal plane is relatively high. For zinc deposition on battery carbon felt using different films, the ratio of the peak intensity corresponding to the (002) crystal plane to the (100) crystal plane (I (002) / I (100) )like Fig.16 The results show that the increase in the amount of Nf-CMC spin coating is conducive to more exposure of the preferred orientation ((002) crystal plane) for uniform zinc deposition. Compared with the P / S-based film, the preferred orientation exposure of the battery using the P / S-Nf-CMC-1000 film in zinc deposition increased by 50%, which is consistent with the SEM image.

[0089] The above characterizations all confirm the excellent effect of the Nf-CMC functional layer in regulating the zinc deposition behavior. The strong electrostatic repulsion between the -COO functional group of CMC and the zincate ions is the direct reason for inducing uniform zinc deposition. Therefore, the surface charge of different films was first measured by a solid surface zeta potential instrument. The test results show that compared with the P / S-based film, as the amount of Nf-CMC spin-coated on the P / S-Nf-CMC film increases, its negative charge is significantly enhanced ( Fig.17 ). According to the Donnan effect, the strong negative charge on the surface of P / S-Nf-CMC film obviously repels the zincate ions with the same negative charge. The quartz crystal microbalance (QCM) was used to capture the different film layers to Zn(OH)4 2- The slight change in the adsorption amount shows that the -COOH functional group of CMC binds to Zn(OH)4 2- There is a strong electrostatic repulsion between them, and the amount of zincate ions adsorbed by the film layer decreases with the increase of CMC content in the film layer ( Fig.18 ).

[0090] In order to further provide theoretical support for the mechanism of uniform zinc deposition in Nf-CMC functional layer, density functional theory (DFT) was used to investigate the interaction between different molecules and Zn(OH)4 2- Potential energy scan ( Fig.19 ). Theoretical calculation results show that CMC and Zn(OH)4 2-The Gibbs free energy value between them is a positive number far greater than 0, indicating that spontaneous reaction is impossible under the action of strong electrostatic repulsion. Therefore, the successful construction of the zinc-phobic functional layer based on electrostatic repulsion is confirmed, which alleviates the "tip effect" and realizes the Zn(OH)4 2- The good distribution of Zn over the entire membrane-electrode interface induces uniform Zn deposition ( Fig. 20 ).

Claims

1. A method for preparing an alkaline zinc-iron flow battery diaphragm, characterized in that: The battery separator includes a porous base membrane, and a modification layer is also covered on the surface of the porous base membrane. The material of the modification layer contains a modification material and a binder, and the modification material is carboxymethyl cellulose; the Zeta potential value of the surface of the alkaline zinc-based liquid flow battery separator is less than -10 mV; The steps include: Step 1, obtaining a porous base membrane; Step 2, dispersing the modified material and the binder in a solvent, and coating the surface of the porous base film, and obtaining the alkaline zinc-iron liquid flow battery separator after drying; the binder is selected from one or more of Nafion, sulfonated polyetheretherketone, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and polyimide; In step 2, the coating method is selected from flat blade coating, spray coating or spin coating; the mass ratio of the modifying material to the binder is 1: (3-8), and the binder accounts for 1-20% of the weight of the solvent; The positive and negative electrolytes used in alkaline zinc-iron flow batteries are K4Fe(CN)6+NaOH and Zn(OH)4 2- +NaOH solution.

2. The method for preparing an alkaline zinc-iron flow battery membrane according to claim 1, characterized in that: The thickness of the porous base film is 20-500 μm; the thickness of the modified layer is 0.1-10 μm.

3. The method for preparing an alkaline zinc-based flow battery separator according to claim 1, characterized in that: The Zeta potential value of the zinc-based flow battery separator surface is less than -20 mV.

4. The method for preparing an alkaline zinc-iron flow battery membrane according to claim 1, characterized in that: The material of the porous base membrane is selected from one or more of polysulfone, polyketone, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, polybenzimidazole, polyvinyl pyridine, polyethylene, polypropylene, chitosan and cellulose acetate.

5. The method for preparing an alkaline zinc-iron flow battery diaphragm according to claim 1, characterized in that: In the step 1, the base membrane is prepared by the following method: dispersing the polymer in an organic solvent as a casting liquid; coating the casting liquid on the surface of the substrate, and performing a film-forming treatment by a phase inversion method to obtain a porous base membrane.

6. The method for preparing an alkaline zinc-iron flow battery membrane according to claim 5, characterized in that: The organic solvent is selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, chloroform or dimethyl sulfoxide.

7. The method for preparing an alkaline zinc-iron flow battery diaphragm according to claim 5, characterized in that: In the phase inversion method, a poor solvent for the polymer is used as a coagulation bath, and the immersion time in the coagulation bath is 1-600 s; in the phase inversion method, after the membrane is treated in the coagulation bath, it is treated with an extraction solvent at a set temperature for a certain time; the set temperature is 20-200°C and the time is 0.5-24h.

8. Use of the battery separator obtained by the preparation method according to any one of claims 1 to 7 in an alkaline zinc-iron liquid flow battery.

9. The use according to claim 8, characterized in that: In the application described, the modified layer faces the negative electrode of the battery.